Inactivation of Staphylococcus aureus in water by pulsed spark discharge - Zheng, Jiansheng (Sci Rep, 2017)
A pulsed spark plasma discharge system was developed and tested as an energy efficient water sterilization method. A 5 log(10) reduction on Staphylococcus aureus concentration of 10(8) CFU/ml was obtained. Complete inactivation was achieved for concentration of 10(6) CFU/ml. Of the various factors generated by an underwater spark discharge, ultraviolet radiation plays a major role. The inactivation was completely suppressed by the addition of 30 mg/L of a soluble sunscreen, Benzophenone-9. Results obtained using the pulsed spark plasma discharge showed that this system has several advantages, such as high energy efficiency, absence of harmful by-products and portability, over the conventional sterilization methods.